Meningkatkan Aktivitas Dan Hasil Belajar Muatan PPKN Tema 6 Menggunakan Model “PINDANG” Pada Peserta Didik Kelas IV SDI Rahmatillah - Sunita Cehsoh; Noorhapizah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The exploration problem is the low movement and learning results of 4th grade understudies at SDI Rahmatillah on PPKn content. This is due to the fact that learning is one-way, makes it easier for students to build their own knowledge, and does not teach students to cooperate with one another. The use of the PINDANG learning model (PBL, PAP, NHT) is one of the efforts made. The reason for this study is to portray educator exercises, increment understudy movement, and understudy learning results. Classroom Action Research (CAR) is used in this study. During the 2022/23 academic year, eight grade IV students at SDI Rahmatillah served as the research subjects. In this study, both qualitative and quantitative data are used. Subjective information were acquired from noticing the exercises of instructors, understudies and learning results. Individual written test measurements in the form of student worksheets and evaluations provided quantitative data. Transformative mixed methods were used to analyze the data, and descriptive and cross-tabulation analysis were used to interpret the results. The teacher's activities at meetings 1 through 3 met the "very good" criteria, according to the findings. At meeting 3, student activity increased to "very active." There is an increase in classical music in meeting 3, which has an effect on student learning outcomes.